The Effect of Book Tax Difference, Foreign Ownership and Transfer Pricing on Tax Avoidance with Profit Management as Moderating Variables - Shabika, Binar; Hariadi, Bambang; Baridwan, Zaki (The International Journal of Accounting and Business Society, 2023)
Purpose — The main objective of this research is to test which is to find out the effect of the book-tax difference, on the other hand, foreign ownership and transfer pricing that is adjusted for tax avoidance, which focuses on the level of profit management which is positioned as an aspect of the moderating variable. Design/methodology/approach — This study focuses on secondary data in the form of samples from several companies engaged in manufacturing, which were listed on the Indonesia Stock Exchange from 2016 to 2019. The companies sampled in this study amounted to 31 companies for 4 years. which is used as a purposive sampling method. The form of data analysis used leads to the Partial Least Square (PLS) method, where it is necessary to use SmartPLS version 3. software. Findings — The study's results found that book-tax difference and transfer pricing influence avoiding taxes. However, the level of foreign ownership does not affect the level of tax avoidance. The research results regarding profit management variables could be moderated regarding the relationship between book-tax difference and transfer pricing on tax avoidance. Still, it cannot relate to the relationship between foreign ownership and tax avoidance practices. Paper type — Quantitative